Influence of sintering duration on crystal phase and optical band gap of Mn3+ -doped willemite-based glass-ceramics - Wei, L. Z.; Mun, Cheongwei; Zakaly, Hesham M. H.; Issa, Shams A. M.; M. Zaid, M. H. (Springer, 2022)
A conventional melt quenching technique was used to successfully fabricate Mn2O3 -doped willemite glass-ceramics (Zn2SiO4:Mn3+) produced from the ZnO-SLS glasses. The results from XRD revealed that willemite crystallization is improved by increasing the sintering duration. It was revealed that, as the sintering duration progressed, the phase formation shifted from amorphous to α-Zn2SiO4 crystal. In addition, the structural growth of willemite phases can be seen using FTIR spectroscopy. The results of UV-Vis spectroscopy indicated that the intense absorption occurs in the UV zone, with wavelengths ranging from 250 nm to 400 nm, while the optical band gap showed a decreasing trend from 3.61 eV to 2.52 eV. These results perfectly established that Mn3+ dopant is potentially beneficial for producing willemite glass-ceramics for optoelectronic applications.